Hepatocyte Growth Factor Attenuates the Severity of Status Epilepticus in Kainic Acid-induced Model of Temporal Lobe Epilepsy by Targeting Apoptosis and Astrogliosis - Sobhan Haghani; Nida Jamali-Raeufy; Motahareh Zeinivand; Soraya Mehrabi; Leila Aryan; Javad Fahanik-Babaei (Basic and Clinical Neuroscience, 2021)
Introduction: Although pharmacotherapy is the most common treatment for epilepsy, proper seizure control is not achieved with current medications. This study evaluated the protective effects of the Hepatocyte Growth Factor (HGF) in a rat model of Temporal Lobe Epilepsy (TLE) and explored possible molecular mechanisms. Methods: A TLE rat model was determined using an intra-hippocampal kainic acid injection (4 μg). Intra-cerebrovascular injection of HGF (6 μg) was performed 30 min before kainic acid injection. Learning and memory impairment were investigated by behavioral tests. The Enzyme-Linked Immunosorbent (ELISA) was used to determine astrogliosis and DNA fragmentation. Changes in neuronal density and mossy fiber sprouting were evaluated by Nissl and Timm staining, respectively. Results: Behavioral assessments indicated that kainate-treated rats presented spontaneous seizures. Moreover, their alternation percentage scores in the Y-Maze test were lower (P<0.001). Likewise, the passive avoidance test confirmed learning disability in Kainate-treated rats (P<0.001). HGF administration reduced the number of spontaneous seizures, alternation percentage score (P<0.001), and cognitive disturbances (P<0.001). The histopathological results also showed that a protected HGF administration contributed to the reduction of neuronal loss in the CA3 subregion of the hippocampus and inhibited the formation of aberrant Mossy Fiber Sprouting (MFS) (P<0.01). Furthermore, the ELISA data indicated a significant decrease in GFAP (P<0.01) and DNA fragmentation (P<0.05) following HGF administration. Conclusion: Our findings demonstrated the validity of HGF in protection against the progression of the kainate-induced TLE in rats. This measure improved learning, cognitive disturbances and inhibited apoptosis and astrogliosis.